Sub-surface investigation in the frontier region of deep-water NW Sabah, Malaysia - Banerjee, A. (European Association of Geoscientists and Engineers, EAGE, 2019)
Worldwide, deep-water exploration has increased significantly during the past decade. However, deep-water is not explored to its full potential and many new discoveries are expected to come in future particularly in SE Asia and East Africa. The petroleum systems of deep-water settings are highly variable in different basins globally. Successful exploration efforts in new basin will depend on improved understanding of the petroleum systems of the explored basins and advanced seismic techniques. Due to high resolution and high-quality recent 3D data in the frontier region of deep-water NW Sabah, we can extract and intricate geological features that are fascinating. Stratigraphic features like mass transport deposits, turbidites, isolated carbonate reef, channel cuts and depositional units namely syn-rift-I, syn-rift-II, Miocene-I, Miocene-II, Mid Miocene Unconformity, pelagic sediments and top of sea bed have been evaluated. Syn-rift-1 sequence (presumably Late Oligocene time) consist of half-graben structures, syn-rift-II unit is overlying the thick syn-sedimentary clastics. Prominent channel cuts are observed on top of syn-rift-II unit. During middle Miocene time, the area experienced carbonate reef buildups on top of pre-existing paleo-highs. Reef build-ups are prominent below the Mid Miocene Unconformity. After the unconformity, the area received thick pelagic sediments. Â© 2019 Asia Petroleum Geoscience Conference and Exhibition, APGCE 2019. All rights reserved.